Occupational fatal injuries associated with mobile hand‐fed wood chippers. Issue 12 (16th October 2018) - Zhu, Julia; Gelberg, Kitty
Abstract : Background: Workers are killed every year in wood chipper‐related incidents despite the repeated hazard warnings. In‐depth, comprehensive, and up‐to‐date studies are needed to identify causal, risk, and contributing factors and assess the current control measures so that an effective and proactive prevention approach can be developed. Methods: Cases were identified from four online databases and manually reviewed to characterize and categorize the fatal events. Results: The study identified 113 wood chipper‐related worker deaths (1982‐2016). The victims were killed in struck‐by (57), caught‐in (41), motor vehicle (7), electrical (4), fall (2), and heat stroke (2) incidents while performing chipper‐related tasks. Conclusions: Chipper‐related worker deaths are preventable. Young and inexperienced workers may be at higher risk for caught‐in deaths. The current feed wheel control devices are not effective for workers to self‐rescue. Fully automatic feed wheel stop devices are needed to prevent caught‐in incidents.